Apex resection in zebrafish (Danio rerio) as a model of heart regeneration: A video-assisted guide - Ellman, Ditte Gry; Slaiman, Ibrahim Mohamad; Mathiesen, Sabrina Bech; Andersen, Kristian Skriver; Hofmeister, Wolfgang; Ober, Elke Annette; Andersen, Ditte Caroline (International Journal of Molecular Sciences, 2021)
Ischemic heart disease is one of the leading causes of deaths worldwide. A major hindrance to resolving this challenge lies in the mammalian hearts inability to regenerate after injury. In contrast, zebrafish retain a regenerative capacity of the heart throughout their lifetimes. Apex resection (AR) is a popular zebrafish model for studying heart regeneration, and entails resecting 10–20% of the heart in the apex region, whereafter the regeneration process is monitored until the heart is fully regenerated within 60 days. Despite this popularity, video tutorials describing this technique in detail are lacking. In this paper we visualize and describe the entire AR procedure including anaesthesia, surgery, and recovery. In addition, we show that the concentration and duration of anaesthesia are important parameters to consider, to balance sufficient levels of sedation and minimizing mortality. Moreover, we provide examples of how zebrafish heart regeneration can be assessed both in 2D (immunohistochemistry of heart sections) and 3D (analyses of whole, tissue cleared hearts using multiphoton imaging). In summary, this paper aims to aid beginners in establishing and conducting the AR model in their laboratory, but also to spur further interest in improving the model and its evaluation.
Created from Fastlane, Scopus look-up
Keywords: Anaesthesia; Apex resection; Heart; Regeneration; Surgical videos; Zebrafish